A Global Analysis of Kinase Function in Candida albicans Hyphal Morphogenesis Reveals a Role for the Endocytosis Regulator Akl1 - Bar-Yosef, Hagit; Gildor, Tsvia; Ramírez-Zavala, Bernardo; Schmauch, Christian; Weissman, Ziva; Pinsky, Mariel; Naddaf, Rawi; Morschhäuser, Joachim; Arkowitz, Robert A.; Kornitzer, Daniel (Frontiers in Cellular and Infection Microbiology, 2018)
The human pathogenic fungus Candida albicans can switch between yeast and hyphal morphologies as a function of environmental conditions and cellular physiology. The yeast-to-hyphae morphogenetic switch is activated by well-established, kinase-based signal transduction pathways that are induced by extracellular stimuli. In order to identify possible inhibitory pathways of the yeast-to-hyphae transition, we interrogated a collection of C. albicans protein kinases and phosphatases ectopically expressed under the regulation of the TET-on promoter. Proportionately more phosphatases than kinases were identified that inhibited hyphal morphogenesis, consistent with the known role of protein phosphorylation in hyphal induction. Among the kinases, we identified AKL1 as a gene that significantly suppressed hyphal morphogenesis in serum. Akl1 specifically affected hyphal elongation rather than initiation: overexpression of AKL1 repressed hyphal growth, and deletion of AKL1 resulted in acceleration of the rate of hyphal elongation. Akl1 suppressed fluid-phase endocytosis, probably via Pan1, a putative clathrin-mediated endocytosis scaffolding protein. In the absence of Akl1, the Pan1 patches were delocalized from the sub-apical region, and fluid-phase endocytosis was intensified. These results underscore the requirement of an active endocytic pathway for hyphal morphogenesis. Furthermore, these results suggest that under standard conditions, endocytosis is rate-limiting for hyphal elongation.